2018
DOI: 10.4103/ajm.ajm_20_18
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency in elderly: Risk factors and drugs impact on vitamin D status

Abstract: Introduction:Vitamin D (VD) deficiency is a major public health problem worldwide. In spite of its high prevalence, particularly among elderly people, VD deficiency is still underestimated by many physicians. Increasingly, VD deficiency is associated with several known geriatric syndromes.Methods:The study sample consisted of 125 patients, aged 75 years and older, admitted to the acute geriatric unit. The plausible association between the serum 25-hydroxyvitamin D [25(OH)D] level and patient age, sex, body mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 76 publications
3
47
1
1
Order By: Relevance
“…The reasons are that compared with young adults, the skin’s capacity to produce vitamin D decreases by 75% at 70 years 29 , 31 . In addition, the elderly have a tendency to wear closed clothing for fear of flu, thus causing minimal exposure to ultraviolet B rays 9 . Their food intake decreases because of a decrease in chewing ability and financial conditions 30 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reasons are that compared with young adults, the skin’s capacity to produce vitamin D decreases by 75% at 70 years 29 , 31 . In addition, the elderly have a tendency to wear closed clothing for fear of flu, thus causing minimal exposure to ultraviolet B rays 9 . Their food intake decreases because of a decrease in chewing ability and financial conditions 30 .…”
Section: Discussionmentioning
confidence: 99%
“…The impaired eating ability in the elderly may also contribute to low concentrations of vitamin D. Therefore, vitamin D deficiency is often associated with various geriatric syndromes. Low concentrations of vitamin D affects the activity of endocrine hormones as in sufferers of diabetes mellitus type 2 (T2DM) and cardiovascular functions, such as coronary artery disease, heart failure, stroke, and hypertension 9 . A recent meta-analysis in individuals with vitamin D deficiency showed oral vitamin D3 reduces both systolic BP (SBP) and diastolic BP (DBP) in individuals with hypertension and decreases SBP in individuals above 50 years.…”
Section: Introductionmentioning
confidence: 99%
“…Female gender is associated with lower vitamin D levels (14.5 ± 10.9 vs. 15.9 ± 9.5, p = 0.007) and independently associated with severe vitamin D deficiency (41.9% vs. 30.4%, p < 0.001; adjusted odds ratio (OR) (95% confidence interval (CI)) = 1.42 (1.08-1.87), p = 0.01). Yet note that a French and Canadian study reported elderly males suffered from a serious vitamin D deficiency as compared to elderly females 56 .…”
Section: Figure 1 Ccfr Is Significantly Higher In Countries With Higmentioning
confidence: 98%
“…To address this question, we compared the prevalence of severe vitamin D deficiency (25-hydroxyvitamin D serum concentration below 12 ng/ ml (30 nmol/l)) and intake levels in different countries 27,28,29,30,31,32,33,34 , with COVID-19 case growth rates and confirmed case fatality rates (cCFR).…”
mentioning
confidence: 99%
“…La nivelul CPA, 1,25 (OH) 2D inhibă exprimarea antigenelor complexului major de histocompatibilitate clasa II și a moleculelor co-stimulatoare și previne diferențierea și maturarea CD, precum și activarea și supraviețuirea acestora, conducând la scăderea antigenului și activarea celulelor T. Mai mult, 1,25 (OH) 2D modulează de asemenea expresia citokinelor derivate de la DC prin inhibarea producției de interleukină (IL) -12 și IL-23 (citokine majore care determină diferențierea Th1 și diferențierea celulelor T helper (Th17)) și îmbunătățirea eliberării IL-10. 14%, rezultate asemănătoare fiind raportate în studiile de specialitate (Kweder H, Eidi H, 2018). Pacienții vârstnici cu deficit sau insuficiență de vitamina D (95%), au avut o prevalență semnificativ mai mare a titrurilor de anticorpi anti tiroid peroxidază (media ATPO), comparativ cu pacienții vârstnici cu niveluri normale ale vitaminei D (5%).…”
Section: Discuțiiunclassified